2020
DOI: 10.1101/2020.09.09.287912
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Disrupting upstream translation in mRNAs leads to loss-of-function associated with human disease

Abstract: Ribosome-profiling has uncovered pervasive translation in 5'UTRs, however the biological significance of this phenomenon remains unclear. Using genetic variation from 71,702 human genomes, we assess patterns of selection in translated upstream open reading frames (uORFs) in 5'UTRs. We show that uORF variants introducing new stop codons, or strengthening existing stop codons, are under strong negative selection comparable to protein-coding missense variants. Using these variants, we map and validate new gene-di… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 67 publications
(70 reference statements)
1
1
0
Order By: Relevance
“…Moreover, conservation analysis of the amino acid sequence, Kozak sequence and stop codon suggests that the amino acid sequence of the uORF1 does not have an evolutionarily ancient function, but its translation process itself may be important. This hypothesis is consistent with D. S. M. Lee et al (2021) analysis of widespread genetic variation affecting translated human uORFs. Authors found that human uORFs were not under selection to maintain amino acid identity, but uORF start codons were conserved and under strong selective pressure.…”
Section: Discussionsupporting
confidence: 91%
“…Moreover, conservation analysis of the amino acid sequence, Kozak sequence and stop codon suggests that the amino acid sequence of the uORF1 does not have an evolutionarily ancient function, but its translation process itself may be important. This hypothesis is consistent with D. S. M. Lee et al (2021) analysis of widespread genetic variation affecting translated human uORFs. Authors found that human uORFs were not under selection to maintain amino acid identity, but uORF start codons were conserved and under strong selective pressure.…”
Section: Discussionsupporting
confidence: 91%
“…In providing the first, to our knowledge, high-throughput functional analysis of natural uORF regulatory activities, our work defines the range of uORF activity and reveals location is as important as Kozak strength in determining yeast uORF functions. Recent work has also highlighted the large number of human uORFs ( Barbosa et al, 2013 ; Calvo et al, 2009 ; Lee et al, 2020 ; McGillivray et al, 2018 ; Wethmar et al, 2010 ). While many aspects of translation initiation are deeply conserved, the mechanisms involved in transcript leader scanning may differ substantially in human cells and tissues.…”
Section: Discussionmentioning
confidence: 99%